Biphenyl-based heat-conducting film with intrinsic self-repairing performance as well as preparation method and application of biphenyl-based heat-conducting film

By introducing biphenyl-type liquid crystal motifs and dynamic imine bonds into the intrinsic thermal conductivity polymer film, combining the reaction technology of thiol and vinyl double bonds, a biphenyl-type thermal conductivity film with high thermal conductivity and self-healing properties was prepared. , solves the problems of reducing thermal conductivity and complex thermal curing of epoxy groups in the prior art, and realizes efficient self-repair and environmentally friendly preparation of materials.

CN119219949APending Publication Date: 2024-12-31GUANGZHOU CHEM CO LTD CHINESE ACADEMY OF SCI +3

Patent Information

Application Number
CN202411115267.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing intrinsic thermal conductivity polymer films produce secondary hydroxyl groups during the preparation process, resulting in a decrease in thermal conductivity, complex thermal curing conditions of epoxy groups and difficult to recover materials, which affects the environment and equipment life.

Method used

By introducing biphenyl liquid crystal motifs and dynamic imine bonds, a biphenyl thermal conductivity film with self-healing properties is prepared by reacting thiol with a vinyl double bond capping prepolymer using thiol to form a crosslinking network structure.

Benefits of technology

The thermal conductivity and mechanical strength of the material are improved, and the self-repairing performance is achieved. The thermal conductivity reaches 0.700W/m·K, the tensile strength recovery rate reaches 73%, and the preparation process is simplified and the impact on the environment is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004993446360000081
    Figure BDA0004993446360000081
  • Figure BDA0004993446360000091
    Figure BDA0004993446360000091
  • Figure BDA0004993446360000092
    Figure BDA0004993446360000092
Patent Text Reader

Abstract

The invention belongs to the technical field of self-repairing polymer heat-conducting materials, and discloses a biphenyl-based heat-conducting film with intrinsic self-repairing performance and a preparation method and application of the biphenyl-based heat-conducting film. The method comprises the following operation steps: introducing a biphenyl liquid crystal unit into a cross-linked structure to endow the material with good heat-conducting property, and further introducing a dynamic imine bond to endow the material with good self-repairing and recoverable properties, the intrinsic high-thermal-conductivity self-repairing thin film material is prepared by simultaneously fixing a biphenyl group and a dynamic imine bond in a cross-linked network through reaction of mercaptan and a vinyl double bond terminated prepolymer, and in addition, the material is endowed with good mechanical strength due to introduction of a mercaptan flexible chain segment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of self-repairing polymer thermal conductive materials, and in particular relates to a biphenyl-based thermal conductive film with intrinsic self-repairing performance, and a preparation method and application thereof. Background Art

[0002] As 5G network base stations, electric vehicle battery systems, chips and other electronic devices, as well as communication equipment and lighting equipment become more and more integrated, miniaturized and multifunctional, these improvements in size and performance result in more heat generated in a smaller volume. If this heat is not removed in time, it will greatly affect the performance of the equipment. Therefore, materials with high thermal conductivity are needed to manage the heat of these devices. It is also worth noting that during use, due to the susceptibility to extreme environmental influences, some cracks or damage are formed. These cracks or damages can cause the material to break or even fail, thus affecting the service life of the equipment. Therefore, the development of self-healing materials with high thermal conductivity is very promising in effectively solving the safety, life and environmental impact of materials.

[0003] Self-healing materials refer to materials that are re-bonded by effective methods to restore them to their original shape or performance. According to the self-healing mechanism, self-healing materials can be divided into exogenous self-healing materials and intrinsic self-healing materials. The self-healing performance of intrinsic self-healing materials relies on the dynamic connection of the material itself, such as imine bonds (CN117757030A) and disulfide bonds (CN117757030A). This simple self-healing mechanism has more potential in the preparation and application of materials. According to different manufacturing methods, thermal conductive polymer materials are mainly divided into two categories, one is intrinsic type and the other is filler type. Filled thermal conductive polymer materials are to change the thermal conductivity of polymer materials by incorporating high thermal conductive fillers into polymer matrix, so they often sacrifice the processing performance and mechanical properties of the material, and also increase the cost of high thermal conductive materials. Intrinsic thermal conductive polymer materials such as CN110229318A and CN111269400A are obtained by changing the molecular structure, segment structure or the arrangement order of molecular chains under external force during the synthesis and processing of polymer materials to obtain a highly ordered cross-linked network structure, thereby suppressing phonon scattering and increasing the thermal conductivity of the polymer material without sacrificing other core properties of the material.

[0004] At present, intrinsic thermally conductive polymer films are mostly obtained by reacting prepolymers terminated by epoxy groups with curing agents containing active hydrogen such as polyamines, phenolic resins or mercaptans. In this case, secondary hydroxyl groups will be produced after the system is cross-linked, which is not conducive to the transmission of phonons, which causes the thermal conductivity of the film prepared by the epoxy group thermal curing method to decrease, and the epoxy group thermal curing conditions are high, the preparation process is complicated, and it is difficult to recycle after the material is formed, which has an adverse effect on the environment. However, thiol-ene click chemistry has a wide range of applications, simple and mild reaction conditions, is hardly affected by the external environment (oxygen and water, etc.), does not use heavy metal catalysts, has a high yield, and has harmless by-products. The product is easy to separate and purify, and does not require solvents or the solvents used are easy to separate.

[0005] Therefore, in order to effectively solve the problems of material safety, lifespan and environmental impact, it is urgent to develop a biphenyl-based high thermal conductive film that is easy to prepare and has excellent intrinsic self-healing properties. Summary of the invention

[0006] In order to overcome the shortcomings and deficiencies in the above-mentioned prior art, the primary purpose of the present invention is to provide a method for preparing a biphenyl-based thermally conductive film with intrinsic self-healing properties; the method is to introduce biphenyl-type liquid crystal units into the cross-linked structure to give the material good thermal conductivity, and further introduce dynamic imine bonds to give the material good self-healing and recyclable properties. By using a prepolymer terminated with a thiol and a vinyl double bond to react, the biphenyl group and the dynamic imine bond are simultaneously fixed in the cross-linked network to prepare an intrinsic high thermal conductivity, self-healing film material, and the introduction of the thiol flexible chain segment gives the material good mechanical strength.

[0007] Another object of the present invention is to provide a biphenyl-based thermally conductive film having intrinsic self-healing properties and prepared by the above-mentioned preparation method.

[0008] Another object of the present invention is to provide an application of the above-mentioned biphenyl-based thermal conductive film with intrinsic self-healing performance.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a biphenyl-based thermally conductive film with intrinsic self-repairing performance comprises the following steps:

[0011] (1) Under a nitrogen atmosphere, 4,4'-biphenyldicarboxaldehyde and 4-amino-3-methylphenol were dissolved in a solvent, a catalyst was added, and the mixed system was reacted at 50° C. to obtain a hydroxyl-terminated prepolymer 1 containing a liquid crystal unit and a dynamic imine bond;

[0012] (2) dissolving the prepolymer 1 obtained in step (1) and the catalyst in a solvent, then adding methacrylic anhydride, and reacting the mixed system in a nitrogen environment at 50° C. to obtain a prepolymer 2 terminated with a vinyl double bond;

[0013] (3) dissolving the prepolymer 2 obtained in step (2) and thiol in a solvent, adding a catalyst, and reacting the mixed system at 100° C. to form a gel and then evaporate the solvent to obtain a biphenyl-based thermal conductive film with intrinsic self-healing properties.

[0014] The solvent in step (1) is anhydrous ethanol; the catalyst is glacial acetic acid, and its addition amount is 0.1-0.5wt% of the mixed system; and the reaction time is 8 hours.

[0015] The molar ratio of 4,4'-biphenyldicarboxaldehyde to 4-amino-3-methylphenol in step (1) is 1:2.03.

[0016] The solvent in step (2) is one or any two of tetrahydrofuran, dichloromethane and diethyl ether; the catalyst is any one of 4-dimethylaminopyridine (DMAP) and polypyrrole (PPY), and the addition amount thereof is 1-3wt% of the mixed system; and the reaction time is 8 hours.

[0017] The molar ratio of the prepolymer 1 to methacrylic anhydride in step (2) is 1:2.04.

[0018] The thiol described in step (3) is one of pentaerythritol tetrakis-3-mercaptopropionate (PETMP) and trimethylolpropane tris(3-mercaptopropionate) (TPTMP); the solvent is N-methylpyrrolidone; the catalyst is one of azobisisobutyronitrile (AIBN) and benzoyl peroxide (BPO), and the addition amount thereof is 1-3wt% of the mixed system.

[0019] The molar ratio of the prepolymer 2 to the thiol in step (3) is 1:(0.5-1).

[0020] The volatilization temperature of the solvent in step (3) is 60-100°C.

[0021] A biphenyl-based thermally conductive film having intrinsic self-repairing properties.

[0022] The above-mentioned biphenyl-based thermal conductive film with intrinsic self-healing properties is used in the fields of flexible electronic devices and smart devices.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] (1) The present invention introduces biphenyl liquid crystal unit into the synthesized molecular structure and the molecular structure is highly symmetrical, thereby improving the thermal conductivity of the material, and the thermal conductivity coefficient reaches 0.700 W / m·K.

[0025] (2) The present invention introduces a dynamic imine bond into the synthesized molecular structure, which gives the material the ability to self-repair. The tensile strength can be restored to 73% before self-repair, that is, the repair efficiency η can reach 73%, solving the problem that traditional thermosetting epoxy resins are difficult to reuse.

[0026] (3) The present invention introduces a vinyl double bond at the end of the synthesized molecular structure, which can undergo a click chemistry reaction with thiol. The reaction conditions are simple and mild, and are almost unaffected by the external environment (oxygen and water, etc.), and no heavy metal catalyst is used. The introduction of the thiol flexible chain segment also enhances the mechanical properties of the material, which can be applied to the field of flexible electronic devices and smart devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the preparation route of the biphenyl-based thermally conductive film with intrinsic self-healing properties prepared in an embodiment of the present invention.

[0028] Figure 2 This is the NMR image of the synthesized prepolymer 1.

[0029] Figure 3 This is the NMR image of the synthesized prepolymer 2. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0031] The raw materials involved in the present invention can be directly purchased from the market, and the process parameters not specifically specified can be carried out by referring to conventional techniques.

[0032] Embodiment 1:

[0033] (1) Preparation of prepolymer 1

[0034] 4,4'-Biphenyldicarboxaldehyde (30 mmol) and 4-amino-3-methylphenol (61 mmol) were dissolved in anhydrous ethanol, respectively. Then, the 4-amino-3-methylphenol solution was poured into the 4,4'-biphenyldicarboxaldehyde solution, and 0.25 wt% glacial acetic acid was dropped into the solution. The mixture was heated at 50 °C and N 2 After stirring under magnetic reflux for 8 hours, the reaction mixture was cooled to room temperature and filtered with a Buchner funnel to obtain a yellow solid product, which was then washed with anhydrous ethanol and dried in a vacuum oven at 60°C for 6 hours to obtain prepolymer 1. Its NMR is shown in FIG. Figure 2 shown.

[0035] (2) Preparation of prepolymer 2

[0036] The prepolymer 1 (25 mmol) obtained in step (1) and 1 wt% of DMAP were dissolved in tetrahydrofuran under nitrogen atmosphere, and then methacrylic anhydride (51 mmol) was added to the reaction system. 2 The reaction mixture was stirred under magnetic reflux for 8 hours under the conditions, and the reaction mixture was cooled to room temperature. The solid product was obtained by filtration with a Buchner funnel, and then washed repeatedly with a saturated sodium bicarbonate aqueous solution and deionized water. Finally, the product was dried in a vacuum oven at 60°C for 8 hours to obtain prepolymer 2. Its NMR is shown in Figure 3 shown.

[0037] (3) Film preparation

[0038] The prepolymer 2 (3 mmol) obtained in step (2) was dissolved in N-methylpyrrolidone, and PETMP (1.5 mmol) and 1 wt% AIBN were added, poured into a polytetrafluoroethylene mold, mixed evenly to form a sol, and reacted at 80°C to form a gel, and then the solvent was evaporated in a vacuum oven to finally form a biphenyl-based thermal conductive film with intrinsic self-healing properties, marked as LM / PETMP-1.

[0039] Example 2: Schematic diagram of the preparation route Figure 1 Shown

[0040] (1) Preparation of prepolymer 1

[0041] 4,4'-Biphenyldicarboxaldehyde (30 mmol) and 4-amino-3-methylphenol (61 mmol) were dissolved in anhydrous ethanol, and then the 4-amino-3-methylphenol solution was poured into the 4,4'-biphenyldicarboxaldehyde solution, and 0.25 wt% glacial acetic acid was dropped into the solution. 2 After stirring under magnetic reflux for 8 hours, the reaction mixture was cooled to room temperature and filtered with a Buchner funnel to obtain a yellow solid product, which was then washed with anhydrous ethanol and dried in a vacuum oven at 60°C for 6 hours to obtain prepolymer 1. Its NMR is shown in FIG. Figure 2 shown.

[0042] (2) Preparation of prepolymer 2

[0043] The prepolymer 1 (25 mmol) obtained in step (1) and 1 wt% of DMAP were dissolved in tetrahydrofuran under nitrogen atmosphere, and then methacrylic anhydride (51 mmol) was added to the reaction system. 2The reaction mixture was stirred under magnetic reflux for 8 hours under the conditions, and the reaction mixture was cooled to room temperature. The solid product was filtered with a Buchner funnel and then washed repeatedly with a saturated sodium bicarbonate aqueous solution and deionized water. Finally, the product was dried in a vacuum oven at 60°C for 8 hours to obtain prepolymer 2. Its NMR is shown in Figure 3 shown.

[0044] (3) Film preparation

[0045] The prepolymer 2 (3 mmol) obtained in step (2) was dissolved in N-methylpyrrolidone, and PETMP (1.5 mmol) and 1 wt% BPO were added, poured into a polytetrafluoroethylene mold, mixed evenly to form a sol, and reacted at 100° C. to form a gel, and then the solvent was evaporated in a vacuum oven to finally form a biphenyl-based thermal conductive film with intrinsic self-healing properties, marked as LM / PETMP-2.

[0046] Embodiment 3:

[0047] (1) Preparation of prepolymer 1

[0048] 4,4'-Biphenyldicarboxaldehyde (30 mmol) and 4-amino-3-methylphenol (61 mmol) were dissolved in anhydrous ethanol, respectively. Then, the 4-amino-3-methylphenol solution was poured into the 4,4'-biphenyldicarboxaldehyde solution, and 0.25 wt% glacial acetic acid was dropped into the solution. The mixture was heated at 50 °C and N 2 After stirring under magnetic reflux for 8 hours, the reaction mixture was cooled to room temperature and filtered with a Buchner funnel to obtain a yellow solid product, which was then washed with anhydrous ethanol and dried in a vacuum oven at 60°C for 6 hours to obtain prepolymer 1. Its NMR is shown in FIG. Figure 2 shown.

[0049] (2) Preparation of prepolymer 2

[0050] The prepolymer 1 (25 mmol) obtained in step (1) and 1 wt% of DMAP were dissolved in tetrahydrofuran under nitrogen atmosphere, and then methacrylic anhydride (51 mmol) was added to the reaction system. 2 The reaction mixture was stirred under magnetic reflux for 8 hours under the conditions, and the reaction mixture was cooled to room temperature. The solid product was obtained by filtration with a Buchner funnel, and then washed repeatedly with a saturated sodium bicarbonate aqueous solution and deionized water. Finally, the product was dried in a vacuum oven at 60°C for 8 hours to obtain prepolymer 2. Its NMR is shown in Figure 3 shown.

[0051] (3) Film preparation

[0052] The prepolymer 2 (3 mmol) obtained in step (2) was dissolved in N-methylpyrrolidone, and TPTMP (2 mmol) and 1 wt% AIBN were added, poured into a polytetrafluoroethylene mold, mixed evenly to form a sol, and reacted at 80°C to form a gel. The solvent was then evaporated in a vacuum oven to finally form a biphenyl-based thermal conductive film with intrinsic self-healing properties, which was labeled LM / TPTMP-1.

[0053] Example 4: Schematic diagram of the preparation route Figure 1 Shown

[0054] (1) Preparation of prepolymer 1

[0055] 4,4'-Biphenyldicarboxaldehyde (30 mmol) and 4-amino-3-methylphenol (61 mmol) were dissolved in anhydrous ethanol, respectively. Then, the 4-amino-3-methylphenol solution was poured into the 4,4'-biphenyldicarboxaldehyde solution, and 0.25 wt% glacial acetic acid was dropped into the solution. The mixture was heated at 50 °C and N 2 After stirring under magnetic reflux for 8 hours, the reaction mixture was cooled to room temperature and filtered with a Buchner funnel to obtain a yellow solid product, which was then washed with anhydrous ethanol and dried in a vacuum oven at 60°C for 6 hours to obtain prepolymer 1. Its NMR is shown in FIG. Figure 2 shown.

[0056] (2) Preparation of prepolymer 2

[0057] The prepolymer 1 (25 mmol) obtained in step (1) and 1 wt% of DMAP were dissolved in tetrahydrofuran under nitrogen atmosphere, and then methacrylic anhydride (51 mmol) was added to the reaction system. 2 The reaction mixture was stirred under magnetic reflux for 8 hours under the conditions, and the reaction mixture was cooled to room temperature. The solid product was filtered with a Buchner funnel and then washed repeatedly with a saturated sodium bicarbonate aqueous solution and deionized water. Finally, the product was dried in a vacuum oven at 60°C for 8 hours to obtain prepolymer 2. Its NMR is shown in Figure 3 shown.

[0058] (3) Film preparation

[0059] The prepolymer 2 (3 mmol) obtained in step (2) was dissolved in N-methylpyrrolidone, and TPTMP (2 mmol) and 1 wt% BPO were added, poured into a polytetrafluoroethylene mold, mixed evenly to form a sol, and reacted at 100°C to form a gel. The solvent was then evaporated in a vacuum oven to finally form a biphenyl-based thermal conductive film with intrinsic self-healing properties, which was labeled LM / TPTMP-2.

[0060] Comparative Example 1:

[0061] (1) Preparation of prepolymer 1

[0062] Terephthalaldehyde (30 mmol) and 4-amino-3-methylphenol (61 mmol) were dissolved in anhydrous ethanol, and then the 4-amino-3-methylphenol solution was poured into the terephthalaldehyde solution, and 0.25 wt% glacial acetic acid was dropped into the solution. 2 After stirring under magnetic reflux for 8 hours under the same conditions, the reaction mixture was cooled to room temperature and filtered with a Buchner funnel to obtain a yellow solid product, which was then washed with anhydrous ethanol and dried in a vacuum oven at 60° C. for 6 hours to obtain prepolymer 1.

[0063] (2) Preparation of prepolymer 2

[0064] The prepolymer 1 (25 mmol) obtained in step (1) and 1 wt% of DMAP were dissolved in tetrahydrofuran under a nitrogen environment, and then methacrylic anhydride (51 mmol) was added to the reaction system. The mixture was stirred under magnetic reflux at 50°C and N2 for 8 hours. The reaction mixture was cooled to room temperature and filtered with a Buchner funnel to obtain a solid product, which was then repeatedly washed with a saturated sodium bicarbonate aqueous solution and deionized water. Finally, the product was dried in a vacuum oven at 60°C for 8 hours to obtain a prepolymer 2.

[0065] (3) Film preparation

[0066] The prepolymer 2 (3 mmol) obtained in step (2) was dissolved in N-methylpyrrolidone, and TPTMP (2 mmol) and 1 wt% BPO were added, poured into a polytetrafluoroethylene mold, mixed evenly to form a sol, and reacted at 100°C to form a gel, and then the solvent was evaporated in a vacuum oven to finally form a film marked as LM / TPTMP-a.

[0067] Comparative Example 2:

[0068] (1) Preparation of prepolymer 1

[0069] 4,4'-Biphenyldicarboxaldehyde (30 mmol) and 4-amino-3-methylphenol (61 mmol) were dissolved in anhydrous ethanol respectively, and then the 4-amino-3-methylphenol solution was poured into the 4,4'-biphenyldicarboxaldehyde solution, and 0.25 wt% glacial acetic acid was dropped. After magnetic reflux stirring at 50°C and N2 for 8 hours, the reactant mixture was cooled to room temperature and filtered with a Buchner funnel to obtain a yellow solid product, which was then rinsed with anhydrous ethanol. Finally, the product was dried in a vacuum oven at 60°C for 6 hours to obtain prepolymer 1.

[0070] (2) Preparation of prepolymer 2

[0071] The prepolymer 1 (25 mmol) obtained in step (1) and 1 wt% of DMAP were dissolved in tetrahydrofuran under a nitrogen environment, and then methacrylic anhydride (51 mmol) was added to the reaction system. The mixture was stirred under magnetic reflux at 50°C and N2 for 8 hours. The reaction mixture was cooled to room temperature and filtered with a Buchner funnel to obtain a solid product, which was then repeatedly washed with a saturated sodium bicarbonate aqueous solution and deionized water. Finally, the product was dried in a vacuum oven at 60°C for 8 hours to obtain a prepolymer 2.

[0072] (3) Film preparation

[0073] The prepolymer 2 (3 mmol) obtained in step (2) was dissolved in N-methylpyrrolidone, and 2 wt% AIBN was added, poured into a polytetrafluoroethylene mold, mixed evenly, and cured at 100° C. for 24 hours to finally form a film marked as LM-1.

[0074] The biphenyl-based thermally conductive films with intrinsic self-healing properties prepared in Example 2 and Example 4, as well as the films obtained in Comparative Example 1 and Comparative Example 2, were characterized in terms of thermal conductivity, mechanical properties, and self-healing properties. The characterization methods and results are shown below:

[0075] 1. Thermal conductivity

[0076] The thermal conductivity of the film was measured by laser flash analysis (instrument model: LFA 467,) and the results are shown in Table 1. Since the designed structure contains biphenyl liquid crystal units and is highly symmetrical, the horizontal thermal conductivity of LM / PETMP-2 and LM / TPTMP-2 reaches 0.526 W / m·K and 0.700 W / m·K, respectively. In addition, because LM / PETMP-2 has more branches, the phonon scattering is more serious, so the thermal conductivity is lower than that of LM / TPTMP-2.

[0077] Table 1

[0078]

[0079] 2. Mechanical properties

[0080] The tensile test was carried out by a computerized tensile testing machine (instrument model: SHT5000). The sample was cut into 40 mm × 10 mm strips according to the tensile standard, and the tensile rate was 10 mm / min. The results are shown in Table 2. The tensile strength of LM / PETMP-2 was 4.74 MPa, and the elongation at break was 42.57%. The tensile strength of LM / TPTMP-2 film was 3.72 MPa, and the elongation at break was 41.6%. Therefore, LM / PETMP-2 exhibited higher tensile strength, and the tensile strength of LM / PETMP-2 was about 1.3 times that of LM / TPTMP-2, which was due to the difference in their cross-linking density.

[0081] Table 2

[0082]

[0083] 3. Self-healing performance

[0084] The 40 mm × 10 mm strip film was cut with a scalpel, and then the tensile strength of the repaired sample was retested after hot pressing at 1 MPa and 100 ° C for 15 minutes by a hot press (instrument model: MAIKESUB38*38 cm flatbed heat press machine), where the repair efficiency η is defined as the ratio of the repaired sample strength to the original tensile strength. The results are shown in Table 3. The presence of the dynamically reversible imine bond gives the material self-healing properties. The original tensile strength of LM / PETMP-2 is 4.74 MPa. With the increase of the number of self-healing cycles, the corresponding tensile strength and elongation at break gradually decrease. The tensile strength after the first self-healing cycle is 3.48 MPa. Similarly, the original tensile strength of LM / TPTMP-2 is 3.72 MPa, and the tensile strength after the first self-healing cycle is 2.7 MPa, both of which are 73% of the original, showing excellent self-healing properties.

[0085] Table 3

[0086]

[0087]

[0088] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a biphenyl-based thermally conductive film having intrinsic self-healing properties, characterized in that The steps include: (1) Under a nitrogen atmosphere, 4,4'-biphenyldicarboxaldehyde and 4-amino-3-methylphenol were dissolved in a solvent, a catalyst was added, and the mixed system was reacted at 50° C. to obtain a hydroxyl-terminated prepolymer 1 containing a liquid crystal unit and a dynamic imine bond; (2) dissolving the prepolymer 1 obtained in step (1) and the catalyst in a solvent, then adding methacrylic anhydride, and reacting the mixed system in a nitrogen environment at 50° C. to obtain a prepolymer 2 terminated with a vinyl double bond; (3) dissolving the prepolymer 2 obtained in step (2) and thiol in a solvent, adding a catalyst, and reacting the mixed system at 100° C. to form a gel and then evaporate the solvent to obtain a biphenyl-based thermal conductive film with intrinsic self-healing properties.

2. The method for preparing a biphenyl-based thermally conductive film with intrinsic self-healing properties according to claim 1, characterized in that: The solvent in step (1) is anhydrous ethanol; the catalyst is glacial acetic acid, and its addition amount is 0.1-0.5wt% of the mixed system; and the reaction time is 8 hours.

3. The method for preparing a biphenyl-based thermally conductive film with intrinsic self-healing properties according to claim 1, characterized in that: The molar ratio of 4,4'-biphenyldicarboxaldehyde to 4-amino-3-methylphenol in step (1) is 1:2.

03.

4. The method for preparing a biphenyl-based thermally conductive film with intrinsic self-healing properties according to claim 1, characterized in that: The solvent in step (2) is one or any two of tetrahydrofuran, dichloromethane and diethyl ether; the catalyst is any one of 4-dimethylaminopyridine and polypyrrole, and the addition amount thereof is 1-3wt% of the mixed system; and the reaction time is 8 hours.

5. The method for preparing a biphenyl-based thermally conductive film with intrinsic self-healing properties according to claim 1, characterized in that: The molar ratio of the prepolymer 1 to methacrylic anhydride in step (2) is 1:2.

04.

6. The method for preparing a biphenyl-based thermally conductive film with intrinsic self-healing properties according to claim 1, characterized in that: The thiol described in step (3) is one of pentaerythritol tetrakis-3-mercaptopropionate and trimethylolpropane tris(3-mercaptopropionate); the solvent is N-methylpyrrolidone; and the catalyst is one of azobisisobutyronitrile and benzoyl peroxide, and the addition amount thereof is 1-3wt% of the mixed system.

7. The method for preparing a biphenyl-based thermally conductive film with intrinsic self-healing properties according to claim 1, characterized in that: The molar ratio of the prepolymer 2 to the thiol in step (3) is 1:(0.5-1).

8. The method for preparing a biphenyl-based thermally conductive film with intrinsic self-healing properties according to claim 1, characterized in that: The volatilization temperature of the solvent in step (3) is 60-100°C.

9. A biphenyl-based thermally conductive film having intrinsic self-healing properties as described in any one of claims 1 to 8.

10. Application of the biphenyl-based thermal conductive film with intrinsic self-healing properties according to claim 9 in the field of flexible electronic devices and smart devices.

Citation Information

Patent Citations

  • Intrinsic thermoplastic heat conducting polyester material, preparation method and application thereof

    CN110229318A

  • Intrinsic thermoplastic thiophene derivative copolymer heat-conducting material as well as preparation method and application thereof

    CN111269400A

  • Preparation method of waterborne polyurethane heat-conducting self-repairing material based on dynamic disulfide bonds

    CN117757030A

Cited By

  • Reprocessable intrinsic heat-conducting cross-linked polyester material as well as preparation method and application thereof

    CN121181863A